2021
DOI: 10.3389/frvir.2021.602087
|View full text |Cite
|
Sign up to set email alerts
|

Changing Between Virtual Reality and Real-World Adversely Affects Memory Recall Accuracy

Abstract: Context-dependency effects on memory exist, whereby people’s context influences their ability to accurately recall items from memory. This effect was not previously studied when considering virtual reality as an environmental context. We show that adverse effects on recall of memorized items exist when changing between virtual and real environments. The effect was not present when memorizing and recall were both done in VR; it appears to be caused by the change of environmental context. This previously unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…and virtually (i.e., VR room condition) reinstated environments, performance in the latter condition was perpetually lower than that in the former. This pattern of results is congruous with findings from studies comparing spatial memory in real and virtual environments (e.g., Lamers & Lanen, 2021;Reichherzer et al, 2018). Seeing that both real and virtual reinstatements produced significantly better spatial memory in comparison to a different or partially reinstated environment, it can be concluded that remembering locations in a virtual replica of the encoding environment may be effective, but not as efficacious as remembering in the actual encoding environment.…”
Section: Spatial Memory In Physically and Virtually Reinstated Enviro...supporting
confidence: 51%
See 3 more Smart Citations
“…and virtually (i.e., VR room condition) reinstated environments, performance in the latter condition was perpetually lower than that in the former. This pattern of results is congruous with findings from studies comparing spatial memory in real and virtual environments (e.g., Lamers & Lanen, 2021;Reichherzer et al, 2018). Seeing that both real and virtual reinstatements produced significantly better spatial memory in comparison to a different or partially reinstated environment, it can be concluded that remembering locations in a virtual replica of the encoding environment may be effective, but not as efficacious as remembering in the actual encoding environment.…”
Section: Spatial Memory In Physically and Virtually Reinstated Enviro...supporting
confidence: 51%
“…Additionally, it examined the use of VR to recreate realworld environments for generating context-dependent spatial memory. Given how previous VR-based context-dependent research tend to converge on memory for words (e.g., Lamers & Lanen, 2021;Shin et al, 2021;Wälti et al, 2019), this study contributes substantially to the existing literature as it provides new insights into the utilization of virtual environments for reinstating the encoding environment and eliciting accurate spatial memory.…”
Section: Chapter Three: Examining Effects Of Environmental Reinstatem...mentioning
confidence: 93%
See 2 more Smart Citations
“…Discussion D3). 1,11,28 Our results provide evidence that contextual support optimises language learning in a manner that leads to high retention-but only when three critical conditions are met: First, participants must subjectively experience the VR-based contexts as actual environments that they feel like they are physically inhabiting during learning (i.e., they must report a high sense of presence). Second, a unique context must support the learning of each language.…”
Section: Discussionmentioning
confidence: 84%